Constitutional Law Accountability for the Forgery of Public Officials' Documents - Ibrohim Ibrohim (Civiliza Publishing, 2026)
The authenticity of documents submitted by public officials constitutes a fundamental element of constitutional governance, administrative legitimacy, and the rule of law. In a democratic legal system, official documents serve not merely as administrative requirements but also as instruments that establish public trust and validate the constitutional authority exercised by state officials. The emergence of allegations involving forged educational or identity documents has raised significant constitutional and administrative concerns, as such misconduct extends beyond criminal liability and directly affects the legitimacy of public office and democratic governance. This study aims to examine the forms of constitutional law accountability applicable to public officials involved in document forgery and to analyze the existing mechanisms for administrative verification and legal responsibility within the Indonesian constitutional framework. The research employs a normative legal method using statutory, conceptual, and case approaches. Primary legal materials consist of the 1945 Constitution of the Republic of Indonesia, Law Number 30 of 2014 concerning Government Administration, Law Number 7 of 2017 concerning General Elections, the Indonesian Criminal Code, and relevant electoral regulations, which are examined through qualitative legal analysis using grammatical, systematic, and teleological interpretation. The findings indicate that constitutional accountability may be implemented through three principal mechanisms: administrative sanctions, the revocation or annulment of administrative decisions based on the contrarius actus principle, and judicial review before the State Administrative Court (Pengadilan Tata Usaha Negara). Nevertheless, the absence of an integrated verification system among state institutions creates legal uncertainty and weakens preventive oversight. This study concludes that strengthening institutional coordination, enhancing the authority of electoral and supervisory bodies, and integrating public administrative databases are essential to ensuring the authenticity of official documents and reinforcing constitutional accountability, legal certainty, and public confidence in state institutions.